Molecules and Prostaglandins Related to Embryo Tolerance - Mayoral Andrade, Gabriel; Vásquez Martínez, Gabriela; Pérez-Campos Mayoral, Laura; Hernández-Huerta, María Teresa; Zenteno, Edgar; Pérez-Campos Mayoral, Eduardo; Martínez Cruz, Margarito; Martínez Cruz, Ruth; Matias-Cervantes, Carlos Alberto; Meraz Cruz, Noemi; Romero Díaz, Carlos; Cruz-Parada, Eli; et al. (Frontiers in Immunology, 2020)
It is generally understood that the entry of semen into the female reproductive tract provokes molecular and cellular changes facilitating conception and pregnancy. We show a broader picture of the participation of prostaglandins in the fertilization, implantation and maintenance of the embryo. A large number of cells and molecules are related to signalling networks, which regulate tolerance to implantation and maintenance of the embryo and fetus. In this work, many of those cells and molecules are analysed. We focus on platelets, polymorphonuclear leukocytes, and group 2 innate lymphoid cells involved in embryo tolerance in order to have a wider view of how prostaglandins participate. The combination of platelets and neutrophil extracellular traps (Nets), uterine innate lymphoid cells (uILC), Treg cells, NK cells, and sex hormones have an important function in immunological tolerance. In both animals and humans, the functions of these cells can be regulated by prostaglandins and soluble factors in seminal plasma to achieve an immunological balance, which maintains fetal-maternal tolerance. Prostaglandins, such as PGI2 and PGE2, play an important role in the suppression of the previously mentioned cells. PGI2 inhibits platelet aggregation, in addition to IL-5 and IL-13 expression in ILC2, and PGE2 inhibits some neutrophil functions, such as chemotaxis and migration processes, leukotriene B4 (LTB4) biosynthesis, ROS production and the formation of extracellular traps, which could help prevent trophoblast injury and fetal loss. The implications are related to fertility in female when seminal fluid is deposited in the vagina or uterus.